Filler-induced heterogeneous distribution of stretch-induced crystallization in natural rubber: An in-situ synchrotron-radiation micro-focused scanning X-ray diffraction study. (21st April 2017) - Chen, Liang; Zhou, Weiming; Su, Fengmei; Zhang, Wenhua; Chen, Pinzhang; Ji, Youxin; Li, Liangbin
Abstract: Crystallinity distribution of natural rubber around filled micrometer-size glass beads under different strains are studied with in-situ micro-focused scanning X-ray diffraction (μ-SXRD), where the glass beads are taken to serve as a model of filler. The experimental results suggest, due to the gradient stress field around the glass bead, the oscillatory distribution of crystallinities around the glass bead tends to form soft-hard double network with multi-scale hierarchical structures and spontaneously responds to external strains. The double network spreads stress in larger region and avoids stress concentration, in which the hard domains with high crystallinities effectively sustain the external stress while the soft domains with low crystallinity store elastic energy. According to the equal strain and equal stress conditions, the quantitative calculation on enhancement factor indicates that the soft-hard double network structure can increase the fracture energy to about three orders of magnitude as comparing to that of structure with homogeneous distribution of crystallinity. Graphical abstract: Due to the gradient stress field around the glass bead, the oscillatory distribution of crystallinities around the glass bead tends to form soft-hard double network with multi-scale hierarchical structures for toughness increase, which spontaneously responds to external strains. The mesh sizes along the long axis of the network structure along its long axis decrease slightly, suggesting denser network structures forming as strains increasing from 4.0 to 5.0. According to the equal strain condition, the quantitative calculation on fracture energy enhancement factors ( R E ) are from 607 to 1444 times magnitude as comparing to that of structure with homogeneous distribution of crystallinity. Highlights: The oscillatory distribution of crystallinity around glass bead is obtained by micro-focused scanning X-ray diffraction. The distribution of crystallinity tends to form soft-hard double network with multi-scale hierarchical structures. The double network increases fracture energy to three orders of magnitude as compared to the homogeneous distribution.